2016
DOI: 10.1039/c5fo01005e
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol-induced presynaptic reduction of glutamate release in the rat hippocampus

Abstract: This study examined whether xanthohumol, a hop-derived prenylated flavonoid present in beer, affects glutamate release in the rat hippocampus. In the rat hippocampal nerve terminals (synaptosomes), xanthohumol inhibited the release of 4-aminopyridine (4-AP)-evoked glutamate and the elevation of cytosolic Ca(2+) concentration, whereas it had no effect on 4-AP-mediated depolarization. The inhibitory effect of xanthohumol on the evoked glutamate release was prevented by removing extracellular Ca(2+), using the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Recently, it has been reported that XN acts at GABAA receptors present in the hippocampal nerve terminals to decrease the Ca 2+ influx through N-type and P/Q-type Ca 2+ channels, which subsequently suppresses the Ca 2+ -calmodulin/PKA cascade to decrease the evoked glutamate release. (33) These results indicated that XN-mediated decrease in the Ca 2+ influx caused the suppression of the PKA cascade in the rat hippocampus, and, therefore, H-89 has been shown to largely prevent the inhibition of glutamate release by XN. In contrast, we found that H-89 did not prevent apoptosis by XN; rather, it synergistically enhanced the antitumor activity of XN.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, it has been reported that XN acts at GABAA receptors present in the hippocampal nerve terminals to decrease the Ca 2+ influx through N-type and P/Q-type Ca 2+ channels, which subsequently suppresses the Ca 2+ -calmodulin/PKA cascade to decrease the evoked glutamate release. (33) These results indicated that XN-mediated decrease in the Ca 2+ influx caused the suppression of the PKA cascade in the rat hippocampus, and, therefore, H-89 has been shown to largely prevent the inhibition of glutamate release by XN. In contrast, we found that H-89 did not prevent apoptosis by XN; rather, it synergistically enhanced the antitumor activity of XN.…”
Section: Discussionmentioning
confidence: 87%
“…These results raised the possibility that the AC/PKA pathway could contribute to preventing apoptosis induced by VCP inhibition and that the activity of AC/PKA pathway in tumor cells could determine sensitivity to XN. Recently, it has been reported that XN acts at GABAA receptors present in the hippocampal nerve terminals to decrease the Ca 2+ influx through N‐type and P/Q‐type Ca 2+ channels, which subsequently suppresses the Ca 2+ ‐calmodulin/PKA cascade to decrease the evoked glutamate release . These results indicated that XN‐mediated decrease in the Ca 2+ influx caused the suppression of the PKA cascade in the rat hippocampus, and, therefore, H‐89 has been shown to largely prevent the inhibition of glutamate release by XN.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the cell proliferation ratio of the GCs was remarkably enhanced as compared to the negative control; conversely, cell apoptosis rate was sharply decreased as GABRA1 expression was silenced. Although the exact roles and regulatory mechanism of GABRA1 and the GABAR in ovarian follicular function remain unclear in chicken, a study reported the inhibitory effect of xanthohumol on evoked glutamate release was antagonized by suppressing the GABAR/Ca 2+ -calmodulin/AC/cAMP/PKA cascade in rat hippocampus [ 73 ]. Moreover, the AC/cAMP/PKA pathway was involved in granulosa cell proliferation and differentiation of ovarian follicles in hen [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in this study three crucial signaling pathways including PPAR signaling pathway, cAMP signaling pathway, and neuroactive ligand-receptor interaction were screened out. Among them, the cAMP signaling pathway was not only involved in the neuroactive ligand-receptor interaction such as the GABAR/Ca 2+ -calmodulin/AC/cAMP/PKA cascade of the GABAergic synapse pathway [ 54 , 73 ], it also provokes a variety of processes required for ovarian follicle growth, selection, differentiation, and maturation [ 74 , 79 ]. As is well known, FSH is essential for reproductive system including steroidogenesis, folliculogenesis, and follicular maturation by interaction with FSH receptor (FSHR) in an endocrine dependent manner [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…2–40 µM) [64,65]. Glutamatergic neurotransmission is involved in normal brain function including cognition, memory and learning processes and in several neurological disorders such as schizophrenia, Parkinson’s disease, epilepsy, stroke and amyotrophic lateral sclerosis [61,66,67].…”
Section: Non-enzymatic Electrochemical Sensorsmentioning
confidence: 99%